2022
DOI: 10.1126/sciadv.abn9516
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering a tripartite landmark in posterior cingulate cortex

Abstract: Understanding brain structure-function relationships, and their development and evolution, is central to neuroscience research. Here, we show that morphological differences in posterior cingulate cortex (PCC), a hub of functional brain networks, predict individual differences in macroanatomical, microstructural, and functional features of PCC. Manually labeling 4511 sulci in 572 hemispheres, we found a shallow cortical indentation (termed the inframarginal sulcus; ifrms ) within PCC tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(93 citation statements)
references
References 94 publications
(169 reference statements)
8
85
0
Order By: Relevance
“…As precision functional data might not always be available for individuals, how might functional organization within PCC be inferred? Our electrophysiological observations are broadly consistent with recent large-scale examination of PCC sulcal anatomy which identified a new tertiary sulcus (inframarginal sulcus) as a useful landmark for the transition from DMN to CCN within dPCC ( Willbrand et al, 2022 ). Further integration of invasive electrophysiology and precision neuroimaging within subjects will be critical for elucidating key features of PCC functional neuroanatomy and its variability across individuals ( Gordon et al, 2017b ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As precision functional data might not always be available for individuals, how might functional organization within PCC be inferred? Our electrophysiological observations are broadly consistent with recent large-scale examination of PCC sulcal anatomy which identified a new tertiary sulcus (inframarginal sulcus) as a useful landmark for the transition from DMN to CCN within dPCC ( Willbrand et al, 2022 ). Further integration of invasive electrophysiology and precision neuroimaging within subjects will be critical for elucidating key features of PCC functional neuroanatomy and its variability across individuals ( Gordon et al, 2017b ).…”
Section: Discussionsupporting
confidence: 89%
“… ( A ) Anatomical locations, normalized to MNI space, of intracranial sEEG depth electrodes targeting the posterior aspect of the cingulate cortex, with the distal contact of probes containing microwires indicated in green. ( B ) Anatomy of human PCC, differentiating dorsal (dPCC) and ventral (vPCC) subregions and demarcating regional sulci following the most recent definitions in PCC ( Petrides, 2018 ; Willbrand et al, 2022 ). ( C ) Attention/Memory Switch task procedure and example stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…After defining LPFC sulci in FreeSurfer, we extracted the following morphological metrics from each sulcal label file: sulcal depth (mm), surface area (mm 2 ), cortical thickness (mm), and local gyrification index (lGI). We selected sulcal depth and surface area as these metrics are prominent features of sulci (Sanides, 1964;Chi et al, 1977;Welker, 1990;Armstrong et al, 1995;Weiner et al, 2014Weiner et al, , 2018Lopez-Persem et al, 2019;Madan, 2019;Petrides, 2019;Weiner, 2019;Miller et al, 2020Miller et al, , 2021aMiller et al, , 2021bNatu et al, 2021;Voorhies et al, 2021;Li et al, 2022;Willbrand et al, 2022aWillbrand et al, , 2022bYao et al, 2022). We further selected cortical thickness and lGI since the longitudinal development of these features was previously analyzed at the lobular level (Alemán-Gómez et al, 2013).…”
Section: Extracting Morphological Features From Sulcal Labelsmentioning
confidence: 99%
“…Mean lGI values (a value comparing the amount of cortex buried within sulci to the amount of cortex on the outer visible cortex, or hull) were extracted with the mris_anatomical_stats function with the pial_lgi flag in FreeSurfer (Fischl and Dale, 2000). As in prior work (Miller et al, 2020;Voorhies et al, 2021;Willbrand et al, 2022aWillbrand et al, , 2022b Although prior work examining sulcal morphology studied sulcal width (for example see Alemán-Gómez et al, 2013;Jin et al, 2018;Carmona et al, 2019), we found that the current toolbox that can extract this information from individual sulcal labels in FreeSurfer (Madan, 2019) failed to obtain the width of many of the smaller sulci in LPFC. Thus, we were not able to examine this feature in the present study.…”
Section: Extracting Morphological Features From Sulcal Labelsmentioning
confidence: 99%
See 1 more Smart Citation